MODERN PSYCHOLOGICAL FACTORS IN THE FORMATION OF IDEOLOGICAL IMMUNITY IN YOUNG PEOPLE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article examines the influence of various alien ideas on the upbringing and development of young people, focusing on the actual psychological methods of forming ideological immunity in the individual